CAROTENOIDS, THEIR SOURCES AND SYNTHESIS - Valieva Nilufar Pulatovna (Innovate Conferences, 2025)
Carotenoids are a diverse group of naturally occurring pigments found in plants, algae, bacteria, fungi, and some animals. They are responsible for the vibrant yellow, orange, and red colors in many fruits and vegetables. Biochemically, carotenoids play essential roles in photosynthesis as accessory pigments, broadening the range of light energy captured by chlorophyll and providing photoprotection against oxidative damage. In humans, certain carotenoids act as precursors for vitamin A, while others function as powerful antioxidants that can neutralize reactive oxygen species. Diets rich in carotenoid-containing foods—such as carrots, tomatoes, bell peppers, spinach, and citrus fruits—have been associated with health benefits, including improved vision, reduced risk of macular degeneration, and enhanced immune function. Industrially, carotenoids are utilized as natural colorants in the food industry, as dietary supplements for their antioxidant properties, and in cosmetics for their protective effects. Ongoing research focuses on optimizing carotenoid biosynthesis through microbial fermentation and genetic engineering to address global nutritional challenges, such as vitamin A deficiency. These developments underscore the importance of carotenoids in maintaining health, advancing food technology, and improving crop biofortification.
Keywords: carotenoids, photosynthesis, antioxidants, vitamin a, carotenes